(Re-)Framing Bede's Historia ecclesiastica in Twelfth-Century Germany: John Rylands Library, MS Latin 182. Issue 1 (1st April 2017) - Pohl
Abstract : This article offers the first comprehensive study of Manchester, John Rylands Library, MS Latin 182, a twelfth-century codex formerly belonging to (and possibly produced at) the Benedictine Abbey of (Mönchen-)Gladbach in Germany. I begin with a full codicological and palaeographical analysis of the entire manuscript, before moving on to a discussion of its contents. These include the Venerable Bede's Historia ecclesiastica gentis Anglorum and the Continuatio Bedae, as well as two hagiographical works copied at the end of the manuscript. I then propose a new possible context of reception for Bede's Historia ecclesiastica during the twelfth century, one that interlinked with the prevalent discourses on secular ecclesiastical lordship and monastic reform at Gladbach, as well as, perhaps, in Germany more widely. In doing so, I essentially argue for the possibility that the Gladbach scribes and their audiences may have used and understood the Historia ecclesiastica not only in the conventional context of 'history' and 'historiography', but also (and perhaps equally important) as an example of the 'golden age' of monasticism, which during the later twelfth century was re-framed and re-contextualised as both a spiritual guide and a source of miracle stories.